صلاحية مقياس أساليب التعلم لانتويستل ومعايير تفسير نتائجه في البيئة الجزائرية - لعزالي, صليحة (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الحالية الى تقنين مقياس أساليب التعلم الذي أعده أنتوستل و آخرون سنة 1979، ثم أجرى "دوف" 1997 مقارنة بين صورتي (1985 ) و (1994) ليقدم صورة نهائية تتكون من 30 بند للمقياس، وهي التي سيتم إستعمالها على عينة هذه الدراسة حيث ترجمها إلى العربية سنة (2006) "السيد محمد أبو هاشم"، وتسعى الدراسة الحالية إلى التحقق من مدى صلاحيته في البيئة الجزائرية، من خلال تطبيقه على عينة تكونت من (256) طالب وطالبة تم اختيارهم بطريقة عشوائية من تخصصات ومستويات مختلفة. وباستخدام معامل ألفا لكرونباخ واختبار "ت" لصدق المقارنة الطرفية، وطريقة التجزئة النصفية، من خلال معادلة سبيرمان –براون، غاتمان، وصدق الاتساق الداخلي، والدرجات المعيارية . وأظهرت النتائج ما يلي: - يتوفر مقياس أساليب التعلم المبني في ضوء نموذج أنتويستيل بدرجة ثبات مرتفعة وباتساق داخلي جيد. - يتوفر مقياس أساليب التعلم المبني في ضوء نموذج أنتويستيل بدرجة صدق مقبولة باستخدام صدق المقارنة الطرفية، الصدق العاملي. - يتوفر المقياس على معايير مناسبة وتتطابق البيانات مع المنحنى الإعتدالي. Abstract The current study aimed to codify the learning styles scale prepared by Entwistle and others in 1979, and then Dove 1997 made a comparison between two pictures (1985) and (1994) to present a final picture consisting of 30 items for the scale, which will be used on this sample to this study was translated into Arabic in (2006) by "Mr. Mohamed Abu Hashem". The current study seeks to verify its validity in the Algerian environment, by appliquedit to a sample of (256) students who were randomly selected from different specializations and levels. by using the Cronbach's alpha coefficient and the "T" test to validate the terminal comparison, the half partition method, through the Spearman-Brown-Gatman equation, validity of internal consistency, and standardized scores. The results of the study are: -The learning styles scale based on the Entwistle model is available with a high degree of stability and with good internal consistency. - The learning styles scale based on the Entwistle model is available with an acceptable degree of validity using the terminal comparison, global honesty. -Scale has appropriate parameters (T.Z), and data conforms to the equilibrium curve.
مقال
Keywords: أساليب التعلم ؛ التقنين؛ نموذج انتويستل؛ طلبة الجامعة; Learning styles; Legalization; Entwistle model; University students